Pengaruh Literasi Keuangan terhadap Perilaku Konsumsi Generasi Milenial di Kota Banda Aceh dengan Faktor Demografis sebagai Variabel Moderator - Hemma Marlenny; Puji Aryani; Muhammad Alfian Aldi (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The millennial generation holds a strategic role in the economy but is prone to consumptive behavior due to low financial literacy. This study aims to analyze the influence of financial literacy on the consumption behavior of the millennial generation in Banda Aceh City, and to test the role of demographic factors (education, occupation, and income) as a moderating variable. A quantitative approach was employed using a survey method on 100 respondents aged 28–43, selected through random sampling. Data were analyzed using simple linear regression and Moderated Regression Analysis (MRA). The results indicate that financial literacy has a significant and positive influence on consumption behavior. Another finding is that demographic factors were unable to significantly moderate this relationship. However, simultaneously, all variables in the model significantly influence Consumption Behavior, contributing 92.8% of the variation. These findings underscore the importance of increasing financial literacy as a dominant strategy for promoting more rational consumption behavior among the millennial generation.